Monitoring Water Flow Speed Below Surface of River Using RS485 Modbus Communication - Mulyaningsih, Try; Marpaung, Jannus; Putra, Leonardus Sandy Ade (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2024)
Continuing water flow rates over time can lead to sedimentation and erosion at the base of the river, potentially damaging ecosystems and infrastructure around the rivers. Monitoring of water flow speeds below the surface of a river needs to be done for monitoring in order to analyze the speed of the water flow that is in the surrounding river. The study develops a monitoring device for water flow speed under the surface using Modbus RS485 communications that are integrated with Internet of Things (IoT) technology to provide water flow information. The research method involves the use of water flow sensors and NodeMCU ESP32. The water flow sensor is capable of accumulating data with measurement accuracy of 96.92% with comparison of a digital flow meter. Tests in the pool are carried out with valve adjustments of 10% to 90% at depths of 15 cm and 45 cm. The pulse generated by the water flow sensor is seen using the Instrustar oscilloscope with the help of the Multi VirAnalyzer application. The test results showed that current speeds range from 0.05 m/s to 0.36 m/s, with pulses increasing as the flow rate increases. As for testing in rivers, sensors can measure current speed up to a depth of 60 cm, with an average speed of 0.06 m/s at a dependency of 15 cm to 0.27 m/s at 60 cm. Test results show that the more in the sensor placement, the higher the measured current speed. The data is displayed on the LCD and Blynk platform, as well as stored in the micro SD.